Quantitative Magnetic Resonance T2 Relaxometry Imaging of Knee Joint Tibia & Femoral Articular Cartilage - Soundarajan, Raj Kumar (British Journal of Healthcare and Medical Research, 2016)
Background: The knee joint is the largest synovial joint in the body with multiple articulating surface. The major consists of the articulation between the femur and tibia, which is weight bearer of the whole body weight and for the balance; and this articulation surface has a major chance of breakdown easily due to various reasons. MR imaging is a powerful tool for the morphologic and compositional imaging of cartilage in the knee for the detection of early cartilaginous degeneration and increased utility for the assessment of cartilage repair techniques. Aim: To obtain T2 relaxometry value of knee joint tibia and femoral articular cartilage & to compare the T2 relaxometry values of the early Osteoarthritic patients with that of the other cause. Material & Methods: 20 patients who presented themselves in Radiology department of either sex whose reports and image data’s are collected prospectively during the study period of December 2011 to February 2012. All the patients’ data within the study period were collected. Patients were selected irrespective of their age group, gender and pathologic findings, a detailed history with various patient’s data includes patient demography, age, sex and the study reports are collected and is entered in a specially designed Profoma. The acquired study data of Sagittal T2 Mapping High Resolution sequence of each patient are then post processed by using a GE Advantage Workstation (version 4.4) and T2 Relaxometry values of various knee joint cartilages (Medial & Lateral femoral and tibial cartilage) are collected by using a special software and is entered in the table. Conclusion: Conventional MRI may not show early cartilage changes; Cartilage edema following trauma (or) Due to osteoarthritis can be picked up early by T2 Mapping. hence it is useful in early patient management. Key words: MRI, Knee joint imaging, tibia and femoral cartilage Imaging, Joint cartilage, T2 Relaxometry, T2 Mapping, osteoarthritis, Knee trauma, Medial and Lateral Tibia and Femoral Cartilage.